Retrospective Analysis of Aceh Government Regulations in Handling Corona Virus Disease 2019 - Alzikri Fakhrurraji (UIN Sunan Gunung Djati, 2021)
The purpose of this study is to conduct a retrospective analysis by identifying the objectives and targets of the Aceh Government regulations in handling Corona Virus Disease 2019, the causes and consequences of the regulations and the problems of policy. Retrosfective analysis in this study applies a qualitative approach and uses descriptive methods. The data collection techniques used were observation, interview and document study. Â The results showed that the objectives of the policies issued by the Aceh Government were to handle Covid-19 and its impact on health, development, the economy and society. The cause of the policy being issued was the increasingly widespread spread of Covid-19. The consequence is a shift in the focus of development plans, changes in the use of budgets and mobilization of resources. The problem with policy is the delay in policy Formulation so that Covid-19 has been in the midst of society. The outreach strategy to the community is still ineffective. Limited resources due to unpreparedness. Low coordination between horizontal agencies and stakeholders.